Open label study of a novel fiber product for bloating, gas, and bowel regularity - Ganz, Alexander S.; Greeley, Brooke; Riggen, James; Riggen, Aundria (Frontiers in Medicine, 2025)
IntroductionThis open-label study evaluated the effects of a novel fiber supplement product, Relievance, on bowel movement regularity and symptoms of bloating and gas in 20 consecutive patients. The product is a commercially available combination of 8 natural fibers and the recommended dosage is approximately 6 grams per serving.MethodsParticipants, presenting with chronic bothersome gastrointestinal symptoms of bloating, gas or bowel irregularity were recruited from an outpatient primary care practice for the study. Participants consumed 6 g of the fiber blend (one heaping teaspoon), one to three times per day, over 6 weeks, and kept diaries on symptoms and number of bowel movements per week. Symptoms were assessed via a 6-point analog scale at baseline and at 6 weeks. Primary endpoints included changes in bowel movement frequency and symptom severity related to gas and bloating.ResultsAt baseline, participants averaged 1.7 bowel movements per week, which significantly increased to 3.2 per week by the study’s conclusion. Symptom severity scores for bloating and gas also improved significantly, decreasing from 3.0 at baseline to 1.5 after 6 weeks. These results demonstrated statistically significant improvements in both bowel regularity and symptom relief. No significant adverse events were reported during the study, highlighting the product’s safety profile.ConclusionThis small, non-randomized prospective trial suggests that Relievance, a proprietary blend of eight different fibers, may effectively enhance bowel movement frequency and alleviate symptoms of bloating and gas. Further randomized controlled trials are warranted to confirm these findings and explore broader applications.